2011
DOI: 10.1016/j.cmet.2011.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of H2O2 within Living Drosophila during Aging Using a Ratiometric Mass Spectrometry Probe Targeted to the Mitochondrial Matrix

Abstract: SummaryHydrogen peroxide (H2O2) is central to mitochondrial oxidative damage and redox signaling, but its roles are poorly understood due to the difficulty of measuring mitochondrial H2O2 in vivo. Here we report a ratiometric mass spectrometry probe approach to assess mitochondrial matrix H2O2 levels in vivo. The probe, MitoB, comprises a triphenylphosphonium (TPP) cation driving its accumulation within mitochondria, conjugated to an arylboronic acid that reacts with H2O2 to form a phenol, MitoP. Quantifying t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
275
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 271 publications
(283 citation statements)
references
References 29 publications
(59 reference statements)
5
275
1
Order By: Relevance
“…S3A). Because oxidative stress increases with age (Balaban et al, 2005;Cocheme et al, 2011), it is tempting to speculate that ROS accumulation owing to aging and ROS generated from alloxan were combined, resulting in higher MDA levels in older mice.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S3A). Because oxidative stress increases with age (Balaban et al, 2005;Cocheme et al, 2011), it is tempting to speculate that ROS accumulation owing to aging and ROS generated from alloxan were combined, resulting in higher MDA levels in older mice.…”
Section: Resultsmentioning
confidence: 99%
“…If all forms of oxidative stress induce the accumulation of tau and tau dysfunction, then the beneficial effects of exercise on AD cannot simply be explained by the causal role of oxidative stress, considering the fact that substantial amounts of ROS are generated during exercise (Rattan & Demirovic, 2010). Even though H 2 O 2 accumulates with aging, it may not be the cause of aging (Cocheme et al, 2011). Some reports have shown that low levels of oxidative stress can extend lifespan (Schulz et al, 2007;Gems & Partridge, 2008;Heidler et al, 2010;Mesquita et al, 2010), indicating that certain conditions present during oxidative stress could delay aging processes.…”
Section: Discussionmentioning
confidence: 99%
“…In Drosophila, hydrogen peroxide production significantly increases during aging (Cochemé et al ., 2011; Sohal & Orr, 2012; Orr et al ., 2013) and increased ROS release during aging was observed from rodent muscles, heart, liver, and brain (Sohal et al ., 1994; Bejma & Ji, 1999; Bejma et al ., 2000; Driver et al ., 2000; Vasilaki et al ., 2006; reviewed in Hekimi et al ., 2011). …”
Section: Testing Predictions Of This Modelmentioning
confidence: 99%
“…We recently disclosed that a mitochondria---targeted arylboronate MitoB can be used to determine directly changes in the concentration of mitochondrial hydrogen peroxide in whole organisms (Figure 7c) (49,50). We have reported the use of MitoB in living flies (Drosophila melanogaster), nematodes (Caenorhabditis elegans), and mice, including providing a detailed step by step protocol (33,49,50), and are now investigating its application to fish. Since these reports include detailed descriptions of how MitoB is employed, we will only provide a very brief overview of the main features of this probe.…”
Section: Mitochondria---targeted Sensorsmentioning
confidence: 99%
“…This was a serious short---coming as ROS are implicated in almost all the diseases of older age and the free radical theory of aging rests on the proposal that damage from mitochondrial ROS accumulates with age. We recently disclosed that a mitochondria---targeted arylboronate MitoB can be used to determine directly changes in the concentration of mitochondrial hydrogen peroxide in whole organisms (Figure 7c) (49,50). We have reported the use of MitoB in living flies (Drosophila melanogaster), nematodes (Caenorhabditis elegans), and mice, including providing a detailed step by step protocol (33,49,50), and are now investigating its application to fish.…”
mentioning
confidence: 99%